The incidence of slip system interactions on the deformation of FCC single crystals: System selection and segregation for local and non-local constitutive behavior. (1st June 2018) - Dequiedt, J.L.
Highlights: System activation under prescribed deformation is influenced by their interactions. Hierarchy of interactions drives system selection. Segregation may take place in the form of band type patterns. These phenomena are justified by linear stability analysis. Gradient plasticity effects penalize some of the segregation modes. Abstract: In single-crystal plasticity, latent hardening between the different slip systems, coming from the interaction of dislocations, strongly influences the mechanical response under prescribed deformation. In this work, the selection of activated systems and their potential segregation in separated zones, taking place in a way which minimizes strain hardening due to system interactions, is investigated analytically for ductile FCC crystals. The crucial role of the respective intensity of the different interactions, estimated by dislocation dynamics simulations, is emphasized and, among them, the very strong collinear interaction between cross slip systems. The evolution of loading paths along lattice axes from symmetric to non-symmetric system activation, which reduces the number of systems, is triggered by uniform instability modes of the initial deformation framework. In the same trend, the segregation of systems in disconnected parts of the crystal, which tends to dissociate primarily strongly interacting pairs, is initiated by plane wave instability modes. Moreover, the introduction of gradient plasticity effects in the form of back stresses functions of the dislocation density tensor, not only introduces an internal length scale for the segregation process, but also brings a selection among the modes in a way which limits the induced incompatibility of the plastic strain field and, hence, the geometrically necessary dislocation (GND) density accumulation.